New record of Miraciidae (Copepoda: harpacticoida) from Tioman waters - Sham, Azrina; Kassim, Zaleha; Ahmad Ishak, Nurul Huda; Ahmad, Zuhairi; Hasnan, Hazwani Hanim (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
A series of meiobenthic sampling were carried in Tioman Island coral area between July to September 2016 and from August until October 2017. Four species from three different genera were identified as family members of Miraciidae Dana, 1846: Robertgurneya smithi Hamond, 1973, Typhlamphiascus typhloides Sars G.O, 1911, Typhlamphiascus lutincola Soyer, 1963 and Delavalia clavus Wells & Rao, 1987. Miraciidae is known as a cosmopolitan family since they dominated all sediment layers and can be distinguished from other families due to the presence of duality ovisac, a rare feature met within harpacticoid. Both Typhlamphiascus were put under different group (1 and 2) due to presence of one or two setae on Enp-3 P4. Presence of spinules on the anterior surface of P1and P4; and spinules laterally align on P1-P4 endopod of Delavalia clavus showed the morphological adaptations of harpacticoid at different habitat. As a comparison with published marine harpacticoid reported from Malaysia, Robertgurneya smithi and Typhlamphiascus typhloides are newly recorded from Malaysian waters.